Resilience and bullying: the possibility of metamorphosis before violence - Vaccari, Vera Lucia (O Mundo da Saúde, 2012)
Resilience and bullying are two terms of recent use for old situations. Resilience refers to human possibility of recovering from adversity. Bullying is a form of physical or verbal violence sometimes by means of Internet resources. It is based on prejudices due to genre, social class, color, race and other factors and occurs in different spaces such as schools. Psychotherapy may contribute for strengthening resilience and interrupting the circle of violence of bullying, with individual or group care for “victims”, “victimizers” and “observers”, family guidance and to teachers, the production of materials and participation in transdisciplinary groups, in a work of promotion of humane values, deconstruction of preconceptions and development of self esteem.